Generalized permanent dentition fluorosis severity becomes less evident over time among a birth cohort - Levy, Steven M.; Warren, John J.; Kolker, Justine L.; Weber-Gasparoni, Karin (Frontiers in Oral Health, 2023)
Objectives There are relatively few cohort studies which have examined changes in fluorosis appearance over time, and none of these have assessed changes in generalized fluorosis. In this analysis, we quantified and assessed changes in multiple measures of generalized fluorosis severity through childhood, adolescence, and young adulthood. Methods Participants were from the Iowa Fluoride Study, a birth cohort recruited from 1992 to 1995. Permanent dentition fluorosis exams were carried out at ages 9, 13, 17, and 23 years using the Fluorosis Risk Index (FRI). Generalized fluorosis was assessed using mean FRI scores at the tooth- and person-level as well as a five-category measure of generalized fluorosis. Generalized fluorosis prevalence and severity was summarized at each time point and differences in adjacent time points were assessed using gamma statistics, signed-rank tests, and plotting changes in generalized fluorosis between adjacent time points. Results We observed a statistically significant decline in the percentage of non-zero mean FRI scores at later exam ages at both the person- and tooth-levels. Based on our five-category generalized fluorosis measure, there were 34.0%–54.1% of participants with generalized fluorosis at baseline for each tooth group, and these percentages declined to 8.9%–27.2% at the age 23-year exam. Conclusions We observed a statistically significant decline in generalized fluorosis severity scores and overall prevalence at later exam ages across all three measures of generalized fluorosis severity. This trend should be accounted for when estimating the prevalence of fluorosis in a population using fluorosis severity data collected in children and adolescents.